Grain Futures Market Response to the Black Sea Grain Initiative - Sandro Steinbach; Yasin Yildirim (German Journal of Agricultural Economics (GJAE), 2024)
This paper assesses the impact of the Black Sea Grain Initiative on the grain futures market. We rely on counterfactual evaluation techniques and detailed futures price series to estimate how corn and wheat futures prices and historical volatility responded to the Grain Deal enforcement, renewals, and termination. Our event study estimates reveal that market participants anticipated the impact of the Black Sea Grain Initiative. This anticipation is evident from the declining trend in grain futures prices aligned with the EU Solidarity Lanes, implying that commodity traders factored in the Grain Deal's effects on grain futures price dynamics. Our analysis also uncovers a limited market response to the subsequent renewals and termination of the Grain Deal. Commodity traders did not perceive the Russian threat of withdrawing from the Grain Deal as a primary market risk. These findings expand our understanding of commodity trader behavior and market sentiment under the Black Sea Grain Initiative.
Keywords: 330; Black Sea Grain Initiative; Commodity Futures Market; Corn and Wheat; Event Studies